Gazprom on the European Market: In Search of the Balance between the Principles of Competition and Energy Security - V. I. Salygin; N. Y. Kaveshnikov (Vestnik MGIMO-Universiteta)
The article analyses the position of Gazprom on the key export market - the market of the European Union. Situation on the EU gas market changed considerably because of an imbalance between supply and demand. Gazprom had to make price concessions for almost all of the main consumers of Russian gas in Europe, and also had to allow European consumers to break one of the key provisions of long-term contracts - "take or pay" clause. Besides disputes at the corporate level significant differences still remain about the well-known Third energy package, which effectively prohibits Gazprom to own and operate gas pipelines on the territory of the EU, as well as binding it to provide a third party access to gas pipelines. The implementation of Third package provisions on function unbundling by some EU Member States in the most rigid version may contradict bilateral international agreements of Russia with the EU Member States, primarily agreements on investment protection. Possible reasons underlying the investigation initiated by the European Commission against Gazprom in connection with a possible violation ofEU competition rules are examined. The paper investigates legal, political and economic aspects of contemporary regime of gas cooperation, particularly restriction of reexport, linkage between gas and oil prices, pricing based on long-term contracts and spot markets. The paper concludes that Russia and the EU need to elaborate a comprehensive document that would ensure the stability of the regulatory environment of energy cooperation and would reflect the balance of interests of producers and consumers. This document should equally ensure highly competitive environment and guarantees of security of supply in the short and long term.